Antoni Tàpies: Collected Essays - Tàpies, Antoni; Sobrer, Josep Miquel (Bloomington Indiana University Press, 2011)
In this insightful collection, one of Spains most influential artists, Antoni Tàpies, reflects on art, life, and politics. A companion to A Personal Memoir (2010), this volume includes essays published in Catalan in six separate books between 1970 and 1999 (The Practice of Art, Art against Aesthetic, Reality as Art, For a Modern and Progressive Art, The Value of Art, Art and Its Places) together with previously uncollected articles, lectures, and other texts. In these essays Tàpies reflects on the social role of art and the artist, discusses the influences on his art, and describes his political and artistic views.
Keywords: art philosophy & esthetics; Philosophy